Boots on the ground: peacekeeping in practice affects, culture, and the Brazilian troops - Pereira, Aline Cirino Gonçalves Tororó (2017)
Along this dissertation, I investigate how the participation of Brazilian Troops in the United Nations Stabilization Mission in Haiti (MINUSTAH) affect and is affected by Brazil’s culture of national security. I conclude that the Brazilian participation in MINUSTAH is informed by Brazil’s national military culture, and has repercussions in the national military praxis